2016
DOI: 10.1016/j.sjbs.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Variation in phenolic compounds and antioxidant activity in apple seeds of seven cultivars

Abstract: Polyphenols are the predominant ingredients in apple seeds. However, few data are available on the phenolic profile or antioxidant activity in apple seeds in previous researches. In this study, low-molecular-weight phenolic compounds and antioxidant activity in seeds, peels, and flesh of seven apple cultivars grown in northwest China were measured and analyzed using HPLC and FRAP, DPPH, ABTS assays, respectively. HPLC analysis revealed phloridzin as the dominant phenolic compound in the seeds with its contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 32 publications
(38 reference statements)
4
63
2
2
Order By: Relevance
“…As has already been demonstrated for other fruits and their corresponding seeds [34], total polyphenol content in the date seeds was higher than in the edible flesh. Their content is higher than even cocoa powder which is classified in fourth place in the database of polyphenols content of food sources [35].…”
Section: Discussionsupporting
confidence: 75%
“…As has already been demonstrated for other fruits and their corresponding seeds [34], total polyphenol content in the date seeds was higher than in the edible flesh. Their content is higher than even cocoa powder which is classified in fourth place in the database of polyphenols content of food sources [35].…”
Section: Discussionsupporting
confidence: 75%
“…The EPR results from this model confirm that the stable radical is located in the seed coat. In addition, previous researches of methanol and hexane extracts of the seeds showed that the seeds contained various polyphenols and fatty acids 5, 6, 10) . The stable radical in the seed can be produced during the scavenging activities of antioxidant compounds in the seeds.…”
Section: Resultsmentioning
confidence: 96%
“…Apples also are distinguished by the highest amounts of phenolic compounds among fruits (Sun et al, 2002). Different apple cultivars as a source of variation of phytochemical content have been widely tested (Wolf et al, 2003;Ceymann et al, 2012;Liaudanskas et al, 2015;Wang et al, 2015;Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%